OBSTRUCTIVE SLEEP APNEA IS AN INDEPENDENT PREDICTOR OF ARTERIAL STIFFNESS IN HYPERTENSIVE PATIENTS. (April 2021) - Rietz, Hermine; Hellqvist, Henrik; Kahan, Thomas; Sommermeyer, Dirk; Hedner, Jan; Grote, Ludger; Spaak, Jonas
Abstract : Objective: Studies have suggested an association between obstructive sleep apnea (OSA) and arterial stiffness. We aimed to further assess this relationship in hypertensive patients. Design and method: In all, 199 patients with hypertension (mean age 57 ± 11 years, 73 females, body mass index 27.9 ± 4.4 kg/m2, office blood pressure (BP) 147 ± 19/89 ± 11 mm Hg) referred for 24-h ambulatory blood pressure monitoring (ABPM, recordings every 20 min throughout) underwent simultaneous over-night polygraphic sleep recording (nasal airflow and finger pulse-oximetry). The number of apneas and hypopneas during sleep per hour were measured (apnea hypopnea index, AHI) as well as the burden of desaturation (oxygen desaturation index, ODI). From ABPM the ambulatory arterial stiffness index (AASI) was calculated as 1 - the regression slope of diastolic on systolic BP. Patients were divided into three groups according to their AHI; AHI <5 (no OSA, n = 75), AHI 5<15 (mild OSA, n = 69) and AHI >15 (moderate/severe OSA, n = 44/11). Also 24-h pulse pressure (PP) was assessed as an indirect marker of arterial stiffness. Results: AASI increased with AHI severity: 0.39 ± 0.14, 0.44 ± 0.13, and 0.46 ± 0.13 in AHI<5, 5<15, and AHI >15, respectively (p = 0.011, by ANOVA). In a multivariate regression model including age, sex, triglycerides (TG), AHI, 24-h systolic BP, 24-h mean heart rate (HR) and diabetes, all but sex, HR and diabetes remained independent predictors for AASI (age p < 0.001, sex p = 0.086, TG p = 0.029, AHI p = 0.015, 24-h systolic BP p = 0.003, 24-h mean HR p = 0.064, diabetes p = 0.070 with R = 0.52, p < 0.001 for full model). Using ODI instead of AHI yielded similar results, though HR was significant (p = 0.022), not TG (p = 0.057). In a similar regression model for describing 24-h PP (replacing 24-h systolic BP with 24-h mean arterial BP), neither AHI, nor ODI, remained independent predictors for 24-h PP. Conclusions: AASI, but not 24-h PP, is independently associated with both AHI and ODI in hypertensive patients together with 24-h systolic BP and age. TG also seems to be of importance in predicting AASI, probably through its association to glucose control. Ongoing work aims to further reveal the potential influence of OSA on arterial function in hypertensive patients.